Employing simulated participants to develop communication skills in medical education: a systematic review - Linder, Ute; Hartmann, Lilly; Schatz, Monika; Hetjens, Svetlana; Pechlivanidou, Ioanna; Kaden, Jens (Simulation in healthcare, 2025)
Summary Statement - Simulated participants (SPs) are often employed to teach communication skills in medical education. Although there is a large number of qualitative and/or noncomparative studies in this field, there is no current evidence for the effectiveness of this teaching method based on quantitative comparative meta-data. The aim of this review was to evaluate the effectiveness of SP-based teaching on patient-centered communication skills in medical education compared with traditional teaching formats such as lecture or peer role play focusing on quantitative and comparative data. According to the Preferred Reporting Items for Systematic Review and Meta-Analysis guidelines, we searched MEDLINE, Cochrane Library, PsycINFO, CINAHL, and ERIC databases for relevant studies published through February 2023. We also conducted hand searches and ancestry searches. Of the 8523 publications identified, 21 studies with 2500 participants and a Medical Education Research Study Quality Instrument score of 13.7 (SD = 1.3, N = 21) were included in the synthesis. Ten studies were eligible for meta-analysis. The pooled effect for communication skills outcomes suggests a medium effect preferring SP-based teaching to traditional teaching formats (standardized mean difference = 0.74, 95% confidence interval = 0.37 to 1.11, I2 = 95%, n = 2061). The heterogeneity is high among the analyzed studies. Further analysis reveals great differences among the studies' characteristics (population, objectives, interventions, control group settings, and outcome measurements).
Gesehen am 03.11.2025